2018
DOI: 10.1021/acs.langmuir.8b00553
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Controlled Noncovalent Functionalization of 2D Materials Based on Molecular Architecture

Abstract: Polymerizable amphiphiles can be assembled into lying-down phases on 2D materials such as graphite and graphene to create chemically orthogonal surface patterns at 5-10 nm scales, locally modulating functionality of the 2D basal plane. Functionalization can be carried out through Langmuir-Schaefer conversion, in which a subset of molecules is transferred out of a standing phase film on water onto the 2D substrate. Here, we leverage differences in molecular structure to spatially control transfer at both nanosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…Striped phases of functional alkanes ( e.g. , phospholipids) assemble on materials such as HOPG via drop-casting from organic solvent , or through Langmuir–Schaefer conversion ,, (see Experimental Methods). In striped phases, alkyl chains assemble parallel to the substrate, , stabilized by a combination of alkyl−π interactions and lateral interactions between alkyl chains within the layer.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Striped phases of functional alkanes ( e.g. , phospholipids) assemble on materials such as HOPG via drop-casting from organic solvent , or through Langmuir–Schaefer conversion ,, (see Experimental Methods). In striped phases, alkyl chains assemble parallel to the substrate, , stabilized by a combination of alkyl−π interactions and lateral interactions between alkyl chains within the layer.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Striped phospholipid surfaces 40−42 on highly ordered pyrolytic graphite (HOPG, Figure 2) provide a useful templating mechanism for controlling assembly of OLAmcapped AuNWs, 39 of particular relevance to examining thermal impacts of trans and saturated chains in OLAm blends. Striped phases of functional alkanes (e.g., phospholipids) assemble on materials such as HOPG via drop-casting from organic solvent 43,44 or through Langmuir−Schaefer conversion 41,45,46 (see Experimental Methods). In striped phases, alkyl chains assemble parallel to the substrate, 43,47−49 stabilized by a combination of alkyl−π interactions and lateral interactions between alkyl chains within the layer.…”
Section: Resultsmentioning
confidence: 99%
“…Diynes including 10,12-pentacosadiynoic acid (10,12-PCD-COOH) assemble into lying-down lamellar phases with paired headgroups on highly oriented pyrolytic graphite (HOPG) and graphene, creating 1-nm-wide stripes of headgroups with pitches (typically 5-8 nm) prescribed by alkyl chain length. [26][27][28][29][30][31][32] Photopolymerization of the diyne produces an ene-yne polymer backbone, which has been extensively examined in the context of molecular electronics, 27,28,33 but also stabilizes the monolayer against solvent exchange. 10, [34][35][36][37][38] Recently, we found that in striped monolayers of diyne phospholipids (e.g., 1,2bis(10,12-tricosadiynoyl)-sn-glycero-3-phosphoethanolamine [diyne PE]; Figure 1A), the terminal ammonium functional group protrudes slightly from the surface, forming a ''sitting'' geometry (Figure 1B).…”
Section: The Bigger Picturementioning
confidence: 99%
“…For electronic modification, long, linear molecules may offer a more promising route than small aromatics for solutionprocessed electronic modification layers; they have already been shown to be good candidates for chemical functionalization of 2D materials, 124,125 and descriptions of electronic modifications are emerging. 126 For example, the alkane n-hexatriacontane (HTC, C 36 H 74 ) crystallizes into well-defined films on graphene, and the presence of a HTC film on a graphene filed effect transistor (FET) improved hole mobility from 17 000 cm 2 V À1 s À1 (without HTC) to 38 000 cm 2 V À1 s À1 , an effect attributed to a reduction in charge density inhomogeneity arising from local lifting of the graphene by the HTC film.…”
Section: Noncovalent Modification Of 2d Materialsmentioning
confidence: 99%